A Map of Days - Riggs, Ransom (The fourth novel of Miss Peregrine's Peculiar Children, 2019)
"After having saved the peculiar world, Jacob Portman is back in Florida with his peculiar friends, where they set out on a journey across America to discover the truth about Jacob's grandfather"--